mRNA Decapping and 5′-3′ Decay Contribute to the Regulation of ABA Signaling in Arabidopsis thaliana - Wawer, Izabela; Golisz, Anna; Sulkowska, Aleksandra; Kawa, Dorota; Kulik, Anna; Kufel, Joanna (Frontiers in Plant Science, 2018)
Defects in RNA processing and degradation pathways often lead to developmental abnormalities, impaired hormonal signaling and altered resistance to abiotic and biotic stress. Here we report that components of the 5'-3' mRNA decay pathway, DCP5, LSM1-7 and XRN4, contribute to a proper response to a key plant hormone abscisc acid (ABA), albeit in a different manner. Plants lacking DCP5 are more sensitive to ABA during germination, whereas lsm1a lsm1b and xrn4-5 mutants are affected at the early stages of vegetative growth. In addition, we show that DCP5 and LSM1 regulate mRNA stability and act in translational repression of the main components of the early ABA signaling, PYR/PYL ABA receptors and SnRK2s protein kinases. mRNA decapping DCP and LSM1-7 complexes also appear to modulate ABA-dependent expression of stress related transcription factors from the AP2/ERF/DREB family that in turn affect the level of genes regulated by the PYL/PYR/RCAR-PP2C-SnRK2 pathway. These observations suggest that ABA signaling through PYL/PYR/RCAR receptors and SnRK2s kinases is regulated directly and indirectly by the cytoplasmic mRNA decay pathway.